Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/advs.202204882
|View full text |Cite
|
Sign up to set email alerts
|

A Balance between Pro‐Inflammatory and Pro‐Reparative Macrophages is Observed in Regenerative D‐MAPS

Abstract: Microporous annealed particle scaffolds (MAPS) are a new class of granular materials generated through the interlinking of tunable microgels, which produce an interconnected network of void space. These microgel building blocks can be designed with different mechanical or bio‐active parameters to facilitate cell infiltration and modulate host response. Previously, changing the chirality of the microgel crosslinking peptides from L‐ to D‐amino acids led to significant tissue regeneration and functional recovery… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Each mouse received three injections of 50 μL hydrogel Implant Extraction and Flow Cytometry Study: At selected time points, the implants were extracted and cell extraction was performed as previously described. [20] An enzymatic digestion with the digestion solution (200 U mL −1 Collagenase IV and 125 U mL −1 DNase I) in RPMI media was used. Samples were stained and prepared following manufacturer instructions, and analyzed on the Cytek NL-3000 Flow Cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Each mouse received three injections of 50 μL hydrogel Implant Extraction and Flow Cytometry Study: At selected time points, the implants were extracted and cell extraction was performed as previously described. [20] An enzymatic digestion with the digestion solution (200 U mL −1 Collagenase IV and 125 U mL −1 DNase I) in RPMI media was used. Samples were stained and prepared following manufacturer instructions, and analyzed on the Cytek NL-3000 Flow Cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…This time point was chosen to explore the interface between the acute and late inflammatory phase of the foreign body response. [ 36 ] The total infiltrated live cell number and CD45+ cell number were similar among all MAP scaffolds groups (Figure 7c,d), which indicated that smaller pore size didn't pose a significant barrier to cell infiltration. We found that there was a size dependent increase in macrophage percentages, with 130 µm MAP scaffolds having the higher number of macrophages (Figure 7e), possibly due to the larger cell size of macrophages among all immune cells.…”
Section: Resultsmentioning
confidence: 87%
“…Only CD11c showed a high negative correlation with the size of the microgels. The uptake of MAP (labeled with AF647) by infiltrated cells was observed, [ 36 ] but there was no high correlation between phenotypical markers and AF647 level. Interestingly, both the pro‐inflammatory marker (iNOS) as well as pro‐regenerative marker (CD206) had a high positive correlation with the sphericity of cells/nucleus and a negative correlation with the area of a cell.…”
Section: Resultsmentioning
confidence: 99%
“…The total infiltrated live cell number and CD45+ cell number were similar among all MAP scaffolds groups (Figure 2b), which indicated that a smaller entry door size didn't pose a significant barrier to the cell infiltration. Macrophages and FcεRI+ cells (such as Langerhan cells, monocytes, mast cells, and other dendritic cells) dominated the immune cell infiltration 45 (Figure 2c). The immune cell recruitment followed a size-dependent manner.…”
Section: Immune Cell Recruitment and Response Followed A Size-depende...mentioning
confidence: 99%